The Meaning Of Filling The Position Of Regional Head Democratically Under The Provisions Of Article 18 Paragraph (4) Of The 1945 Constitution - Maranjaya, Abdul Kahar (Faculty of Law, Universitas Pekalongan, 2024)
The various laws governing local elections are; i).Law No. 1 of 2015 on the establishment of government regulations in lieu of Law No. 1 of 2014 on the election of governors, regents, and mayors into law. ii).Law of the Republic of Indonesia No. 8 of 2015 on amendments to Law No. 1 of 2015 on the establishment of government regulations in lieu of Law No. 1 of 2014 on the election of governors, regents, and mayors into law; iii). Constitutional Court Decision No. 100/PUU-XIII / 2015 related to the law of the Republic of Indonesia No. 8 of 2015 on amendments to Law No. 1 of 2015 on the determination of government regulations in lieu of Law No. 1 of 2014 on the election of governors, regents, and mayors into law; iv). Law No. 10 of 2016 on the Second Amendment To Law No. 1 of 2015 on the establishment of government regulations in lieu of Law No. 1 of 2014 on the election of governors, regents, and mayors into law v). Law No. 6 of 2020 on the establishment of government regulations in lieu of Law No. 2 of 2020 on the Third Amendment to Law No. 1 of 2015 on the establishment of government regulations in lieu of Law No. 1 of 2014 on the election of governors, regents, and mayors into law into law. The research method used is normative legal research with a statute legal approach and a conceptual approach. the results of this study are Head Department filling model Regions experienced changes from time to time influenced by the political law of forming laws, regional privileges, and regional autonomy system adopted by the prevailing regime of government. Provisions on filling the position of Regional Head contained in Article 18 paragraph (4) of the law of the Republic of Indonesia in 1945, not should be interpreted by direct election by the people in each region, but can different, especially for special areas.